SRM dataset of the proteome of inactivated iron-sulfur cluster biogenesis regulator SufR in Synechocystis sp. PCC 6803 - Linda Vuorijoki; Pauli Kallio; Eva-Mari Aro (Elsevier, 2022)
This article contains SRM proteomics data related to the research article entitled ”Inactivation of iron-sulfur cluster biogenesis regulator SufR in Synechocystis sp. PCC 6803 induces unique iron-dependent protein-level responses”[1]. The data described here provide comprehensive information on the applied SRM assays, together with the results of quantifying 94 Synechocystis sp. PCC 6803 proteins.  The data has been deposited in Panorama public  (https://panoramaweb.org/labkey/SufR) and from PASSEL under the PASS00765 identifier (http://www.peptideatlas.org/PASS/PASS00765).